Musicalidades brasileiras: expressões, vivências, relações, tensões e resistências no cenário musical urbano dos anos de 1960-1990 - Cardoso, Marilu Santos (2019)
This ongoing research aims at hashing out the Brazilian musicality: expressions, experiences, interface, tension and resistance in 1960-1990 unban scene. To achieve this, the musicians, composer and singers whose trajectory have drown my attention to their perspective about the present, as well as the viewpoint assumed by them through the former period investigated was established as subjects/objects of the research. These musicians are: Airto Moreira, Geraldo Vandré, Hermeto Pascoal, Heraldo do Monte, Sérgio Ricardo, Sidney Miller e Theo de Barros. Men who have experienced Brazilian music and culture, contemplating their different aspects and specialness. All of them had some interaction in some moments but have followed their solo career. The relationship between music and politics is central to the investigation, being the oral narratives essentials sources for the achievement of this study. In the face of the plurality of experiences, I tried to emphasize their connection with music, as well as the multiple ways their work have been undergone by the relation established with the Brazilian cultural industry, which interfere in the creative process, production, media placement and reception of them. It is important to highlight that the project and the position of resistance are constituent parts in the choice of this theme, as well as the considerations and records presented here